Kajian Spektrum Sinar-X 6 MV Menggunakan Simulasi Monte Carlo - Anam, Choirul (BERKALA FISIKA, 2011)
X-ray spectra produced by Elekta Linac for 6 MV beam have been evaluated using Monte Carlo simulation. In this simulation, Linac head was modeled using BEAMnrc code. X-ray sepctra, fluence vs position, and energy fluence vs position were determined using BEAMDP code. In this simulation, the SSD (source skin distance) was 90 cm and the field size of radiation was 10 x 10 cm2. Energy electrons arriving at the target (incident electron) was varied 5.7 MeV, 6.0 MeV, 6.3 MeV and 6.6 MeV. As for the radial intensity, FWHM values ​​varied 1.0 mm, namely 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm. X-ray spectra were determined at the surface of the phantom. Iit was found that the curve 6 MV X-ray spectra has a shape not symmetry with an average energy of about 2 MeV. In the spectra there is no energy X-ray radiation value exceeds the kinetic energy of incident electrons. X-ray spectra is not affected by the width of electron beam striking on the target. if the electron energy increases, it will generate increased fluence and energy fluence, but no effect on the penumbra region (the edge of field size). If the electron beam width increases, it will result in the radiation field edge becomes less sharp or penumbra widening. Keywords — Monte Carlo Simulation, X-ray spectra, Linear Accelerator